TOWARDS A NEW CONCEPTUAL FRAMEWORK OF E-MAINTENANCE - Vasiljevic, D.; Cvetic, B. (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: The aim of this paper is to design a conceptual framework of e-maintenance based on a hybrid system approach, and to analyse its characteristics and the effects of the system on maintenance and business performances. The Interactive Electronic Technical Manual is recognized as an effective e-learning tool and the main maintenance-related component of the framework. The major benefits of the developed framework are an automated process of data entry, maintenance of data consistency, decreased data redundancy, and customised reporting. The proposed conceptual framework should be suitable for maintenance and logistics engineers who intend to develop e-maintenance in industrial sites. AFRIKAANSE OPSOMMING: Die doelwit van hierdie artikel is om